2017
DOI: 10.3390/ma10080966
|View full text |Cite
|
Sign up to set email alerts
|

Esterification Mechanism of Bagasse Modified with Glutaric Anhydride in 1-Allyl-3-methylimidazolium Chloride

Abstract: The esterification of bagasse with glutaric anhydride could increase surface adhesion compatibility and the surface of derived polymers has the potential of immobilizing peptides or proteins for biomedical application. Due to its complicated components, the esterification mechanism of bagasse esterified with glutaric anhydride in ionic liquids has not been studied. In this paper, the homogenous esterification of bagasse with glutaric anhydride was comparatively investigated with the isolated cellulose, hemicel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Other reports in the literature also con rmed the peak at 1571 cm − 1 for stretching carboxylate groups (Ma et al 2012;Wang et al 2017). It might establish an equilibrium reaction in the presence of water.…”
Section: Ftir Characterizationmentioning
confidence: 52%
See 1 more Smart Citation
“…Other reports in the literature also con rmed the peak at 1571 cm − 1 for stretching carboxylate groups (Ma et al 2012;Wang et al 2017). It might establish an equilibrium reaction in the presence of water.…”
Section: Ftir Characterizationmentioning
confidence: 52%
“…The grafting of the cellulose surface by the anhydride groups initiates a nucleophilic attack of the more accessible hydroxyl group of cellulose to the carbonyl group of glutaric or succinic anhydride molecule. Then, the ring-opening of the as-obtained intermediate creates glutarylated or succinylated cellulose (Wang et al 2017). Glutaric anhydride has a pyranose ring structure, while succinic anhydride has a furanose ring structure.…”
Section: Degree Of Substitution (Ds)mentioning
confidence: 99%
“…This allows the calculation of the one-dimensional free energy change, known as potential of mean force (PMF). , For this study, energy minimizations were performed on the reactant ( d -glucose and acetic anhydride) and product (acetylated d -glucose at the C6 position and acetic acid) structures in various conformations. The C6 position in d -glucose (Figure d) was selected due to its susceptibility to acetic anhydride attack, as reported in several studies. , HBDs facilitate proton dissociation and complex formation with the reactants. However, experimental studies have shown that ethylene glycol and urea HBDs do not provide a sufficient concentration of H + to significantly alter the neutral mechanism in other reactions .…”
Section: Theoretical Methodsmentioning
confidence: 99%
“…Citric acid was also studied as a catalyst for cellulose acetylation [ 28 ]. Alternatively, CNCs can be esterified with glutaric anhydride in an ionic liquid medium [ 29 ].…”
Section: Introductionmentioning
confidence: 99%